Using small hardwood logs to produce liquid fuels and electricity. Issue 3 (2nd July 2016) - Cummins, J.; Skennar, C.; Capill, L.; Cassidy, M.; Palmer, Graeme
ABSTRACT: The production of larger high-value sawlogs from native forests or plantations requires removal of smaller and defective stems by thinning. This provides space for residual stems to grow into larger high-value forest products. An acceptable return on investment from growing hardwoods in plantations requires that some value is returned from thinned wood. Thus new markets are needed for small-diameter hardwood forest products. The production of fuel and energy from woody biomass offers one such opportunity. The potential value added by converting wood to high-energy liquid fuels such as petroleum or aviation fuel and the prospect of diminishing mineral oil supplies justifies research in this field. The Fischer Tropsch (FT) synthesis appears to offer substantial advantages in the capacity to break down biomass by thermal decay and chemical reformation to form a range of high energy/value fuels. In addition, these processes are exothermic, and create opportunities to produce process heat, electricity and fuels concurrently. The returns on electricity production are optimised where fuel costs are low and where the electricity produced can be used to displace retail purchasing (self-supply). The costs of harvest and transport of biomass prevent profitable production of electricity and sale at wholesale prices. The primary research goal relating to the development of biomass to fuel and electricity production is the adaption of known processes to scales dictated by biomass supplies. However, to self-supply and disconnect from the national grid implies that power plants must incorporate redundancy so energy supply can be secured. This must be achieved within acceptable capital cost limits.